PENGARUH RESILIENSI TERHADAP KUALITAS HIDUP PADA MAHASISWA FATHERLESS - Shafa Khairunnisa Az Zahra; Pratiwi, Lila (Research Institute and Community Engagement of UIN MADURA, 2025)
The absence of a father role in a child's life is a complex social problem that has a broad impact on the development of students in the early adult phase. Fathers play an important role as caregivers, protectors, and role models in the formation of children's character. However, when the father's presence is not optimal, a condition known as fatherlessness can occur. The purpose of this study is to examine the extent of the influence of resilience on the quality of life in college students who experience fatherlessness. This study involved 129 active university students in Jakarta who experienced fatherlessness and were aged between 18 to 25 years. The method in this study uses a quantitative approach with incidental sampling techniques. The research instruments consisted of the Connor Davidson Resilience Scale (CD-RISC) with reliability (α = 0.907) and the Indonesian Quality of Life Scale (α = 0.888). Data were analyzed using simple linear regression test with IBM SPSS version 25. The results of the analysis showed that resilience has a significant positive influence on the quality of life of fatherless students, with a contribution of 16.9%. Therefore, the results of this study emphasize the important role of resilience in improving the quality of life of college students who experience fatherlessness.